Influência da dieta hipoproteica sobre as respostas comportamentais de ratas lactantes e repercussão comportamental nos filhotes machos - Batista, Tatiane Helena (2015)
The maternal behavior (MB) is crucial for the appropriate development of the offspring, and alterations in this kind of behavior may lead to behavioral changes in the offspring as adults. Therefore, the objective of this study was to evaluate the effect of protein restriction during pregnancy on MB and its consequences in pups. For this purpose, Wistar rats were treated with protein restricted diet (6%) from day 0 to 15th of pregnancy (DP). After the birth of the pups, the MB was recorded daily from the 2th to 8th day of lactation (DL); furthermore, the MB analysis after maternal separation was performed, on the 9th DL. These same MB analyzes were also held in cross-fostering groups – adoptive mothers treated with hypoproteic diet caring for pups whose mothers received normal protein diet (22% protein), and adoptive mothers who received normal protein diet caring for pups whose mothers received restricted protein diet during pregnancy. In addition, behavioral tests of open field and elevated plus-maze (EPM) were performed on the mothers of the groups with or without cross-fostering. The offspring from the MB were also used as adults for behavioral analysis of open field and elevated T-maze (ETM) tests in two conditions, submitted or not to restraint stress. Additionally, the adult pups were also evaluated as for the autonomic responses before, during and after exposure to restraint stress. The results show that pups of hypoproteic mothers, when maintained by their hypoproteic mothers, present a predictive behavior of anxiety reduction during adulthood, even after the stress. This may be due these mothers are more motivated to build the nest, and that these puppies, due intrauterine protein restriction, demonstrated hyporesponsiveness when exposed to adverse situations in adult life. In addition, after cross-fostering, there were alterations in behavior as well as in male offspring as adults, thus changing behavioral and autonomic responses of pups of hypoproteic mothers maintained by normoproteic mothers.